PENYULUHAN HUKUM MENGENAI KEAMANAN LINGKUNGAN TEMPAT TINGGAL DI RT.001 RW.002 KELURAHAN MARIO KECAMATAN MARISO KOTA MAKASSAR - Tangko, Lidwina Aprilliana Allo (Batara Wisnu : Indonesian Journal of Community Services, 2023)
The security situation of the environment where residents live in RT.001/RW.002, Mario Village, Mariso District, Makassar City has not been able to provide a sense of security and comfort due to the fact that there are several community members who invite residents from other areas to come together and drink alcoholic beverages, even The large number of boarding houses in RT.001/RW.002 Mario Village, Mariso District, Makassar City has made residents very wary of the large number of new arrivals living in these boarding houses. There are problems related to the security of the living environment, so there is a need for legal empowerment as an effort to increase awareness of maintaining environmental security and community discipline in creating a comfortable place to live. Residents of the RT.001/RW.002 Mario Village, Mariso District, Makassar City received new information and knowledge about the importance of maintaining the security of their residential environment, carried out Siskamling in the form of Night Patrols to increase awareness, implemented a curfew and provided a guest book by the RT Head. This activity plan can be implemented well after prior coordination and approval from local community stakeholders. This activity takes the form of an interactive dialogue, which is packaged in a discussion and question and answer session to accommodate the responses and opinions of the local community. After that, the community activity ended with the responsibility being given to supervise the dissemination of this information, so that it was hoped that it could increase awareness regarding the safety of the living environment